2018
DOI: 10.1093/cid/cix952
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Received by Adolescents Undergoing Voluntary Medical Male Circumcision: Moving Toward Age-Equitable Comprehensive Human Immunodeficiency Virus Prevention Measures

Abstract: BackgroundThe minimum package of voluntary medical male circumcision (VMMC) services, as defined by the World Health Organization, includes human immunodeficiency virus (HIV) testing, HIV prevention counseling, screening/treatment for sexually transmitted infections, condom promotion, and the VMMC procedure. The current study aimed to assess whether adolescents received these key elements.MethodsQuantitative surveys were conducted among male adolescents aged 10–19 years (n = 1293) seeking VMMC in South Africa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Older adolescents were more likely to receive HIV education and testing, condom demonstrations, and condoms to take home than younger boys. Observations confirmed that condom demonstrations occurred less frequently for younger adolescents [ 24 ]. Older adolescents had greater knowledge of the importance of condom use, about having fewer sex partners, and about the importance of faithfulness [ 25 ].…”
Section: Lessons Learnedsupporting
confidence: 57%
See 3 more Smart Citations
“…Older adolescents were more likely to receive HIV education and testing, condom demonstrations, and condoms to take home than younger boys. Observations confirmed that condom demonstrations occurred less frequently for younger adolescents [ 24 ]. Older adolescents had greater knowledge of the importance of condom use, about having fewer sex partners, and about the importance of faithfulness [ 25 ].…”
Section: Lessons Learnedsupporting
confidence: 57%
“…When researchers observed interactions, they found that counselors demonstrated respectful interest with young clients, and they used supportive body language, indicating that they were likely to be perceived as supportive by adolescents engaged in the service [ 24 ]. Nearly all adolescents (97%) reported high satisfaction with VMMC, and >72% were very likely to recommend VMMC to their peers [ 23 ].…”
Section: Lessons Learnedmentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential to reach adolescents aged 10–14 years as their in-depth knowledge of sex and ways to prevent HIV acquisition, including the use of condoms, is often quite low; condom use among sexually active males in this age group is typically lower than that of older adolescents [ 31 , 32 ]. As outlined in other findings from this study population [ 33 ], younger adolescents aged 10–14 years received fewer elements of the minimum package overall than did 15- to 19-year-olds, despite the fact that adolescents stated they wish they had more of this information.…”
Section: Discussionmentioning
confidence: 51%